2019
DOI: 10.1016/j.eats.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Knotless, Tensionable All-Suture Anchor Bankart Repair

Abstract: Surgical management for glenohumeral instability has advanced to provide stronger fixation and to be less invasive. Arthroscopic suture anchor repair has been the gold standard for isolated capsulolabral tears over the years. Despite the ability of the solid suture anchors to handle physiologic load, they can present challenges such as chondral damage due to anchor size and imperfect angulation, osteolysis, anchor breakage, revision drilling, difficulty of revision surgery with accompanied bone loss, and compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…This is one of the reasons why we prefer all suture anchor in an active young patient. Not only is the anchor good for the young with good quality of bone but also suitable for older patients as well [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the reasons why we prefer all suture anchor in an active young patient. Not only is the anchor good for the young with good quality of bone but also suitable for older patients as well [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sutures were secured with a sliding knot followed by alternating half-hitches with attention to place the knot away from the articular surface. 14…”
Section: Suture Anchor Placementmentioning
confidence: 99%
“…Upon completion, the portals are closed with 2-0 monofilament suture and sterile dressing and chest strapping bandage was applied. 14 Post-operative care : Arm chest bandage was applied. Stitch was off at 14 days.…”
Section: First Suture Anchor Placementmentioning
confidence: 99%
“…S oft-tissue repair with all-suture anchors has grown in popularity because of the sutures' ability to preserve bone stock, improve postoperative imaging after surgery, and facilitate easier revision surgery if necessary. [1][2][3][4] These all-suture anchors consist of a soft upper section and a stiff lower section that allow the anchor to increase in diameter when tension is applied, securing it to the cortical bone. Owing to the soft component of all-suture anchors, secure fixation in the intramedullary space must be provided by gentle, simultaneous pulling of both suture limbs to have the anchor seated against the cortex.…”
mentioning
confidence: 99%
“…Owing to the soft component of all-suture anchors, secure fixation in the intramedullary space must be provided by gentle, simultaneous pulling of both suture limbs to have the anchor seated against the cortex. 1 Previous studies have addressed concerns about the fixation strength of all-suture anchors owing to their soft component and have shown that the ultimate failure load of all-suture anchors is similar to that of established solid suture anchors. [5][6][7][8] However, all-suture anchors have been shown to have different biomechanical properties than solid suture anchors in terms of greater initial displacement owing to their soft component, achievement of higher ultimate loads to failure in high-density bone, and last, stronger pullout strength in the physiological traction direction of the capsulolabral complex in labral repairdor of the supraspinatus in rotator cuff repairdrather than in the knot-tying direction.…”
mentioning
confidence: 99%